Virtual education from the perspective of the intersubjectivity of learning (Revista Científica Compendium, 2022)
The pandemic has brought a new way of continuing the educational process, moving from face-to-face to virtual classes. The research reflects on the intersubjectivity of communication in virtual education in relation to educational academic results in Chile. The objective of the work was to analyze the implementation of virtual education through the intersubjectivity of learning, in relation to attendance, passing and failing in the year 2021 in Chile. The classes were conducted in the distance education modality. The methodology of the research is mixed: of bibliographic review and data collected from the Chilean Ministry of Education. The analysis was carried out with the statistical program SPSS. The main result is that academic communication is fundamental for learning, it is based on class attendance and positive impact on approval, affected during the time of pandemic. Conclusion: both in achievement-based learning expectations, as well as technological advances used by students and teachers, the pedagogical communication is necessary for better academic results.
Keywords: Education; Virtuality; Intersubjectivity; Technologies